A Survey on Reducing Handoff Latency in WLAN - Sarddar, D; Ghosh, U; Pandit, Rajat (International Journal of Computer Sciences and Engineering, 2019)
Advance Wireless communication offers fast data transfer rate,Quality of Service(QoS)and capability to travel or roam heterogeneous networks. .A Handoff technique is an important issue in Modern wireless mobile networks. Handoff delays make a serious problem,our intention is always reduce handoff delay or latency. There are several research has been done in past few years to reduce the handoff delays occur in the multiple levels of wireless communication. Because of the movability of devices handoff is an important aspect in Wireless Local Area Network(WLAN) and cellular communications or cellular networks. In WLAN this aspect is much more important due to bounded range of Access Point (APs), WLAN also provides sufficient bandwidth for real time streaming services. In the literature multiple handoff schemes have been proposed to reduce the handoff latency and also support fast handoff in IEEE 802.11 wireless networks. In this paper, we review these handoff schemes and explore their utility and downside qualitatively. In this paper, Our aim is to make a spadework for future research on reducing the handoff latency and give emphasis on requirement of fast handover for seamless connectivity. We comprise here various techniques to reduce handoff delays. Some future research ideas are also suggested here.